2002
DOI: 10.1161/01.atv.0000035521.22199.c7
|View full text |Cite
|
Sign up to set email alerts
|

Nonfasting Apolipoprotein B and Triglyceride Levels as a Useful Predictor of Coronary Heart Disease Risk in Middle-Aged UK Men

Abstract: Objective-The Apolipoprotein-related Mortality Risk (AMORIS) study concluded that the apolipoprotein (apo)B/apoA-I ratio was the best predictor of coronary heart disease (CHD) risk. We have compared the pairwise combinations of total cholesterol, triglycerides (TGs), apoB, high density lipoprotein (HDL) cholesterol, low density lipoprotein cholesterol, and apoA-I on CHD risk prediction in middle-aged men. Methods and Results-Healthy middle-aged men (nϭ2508), free of CHD at baseline, were examined prospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
141
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(156 citation statements)
references
References 26 publications
11
141
1
3
Order By: Relevance
“…Two important markers for CVD, Apo-A and Apo-B, are considered to be better predictors of CVD risk than serum HDL and LDL levels [20,26,51]. Similarly, the Apo-B/ Apo-A ratio is considered to be a better predictor of CVD risk than the total cholesterol/HDL ratio [23,26].…”
Section: Discussionmentioning
confidence: 99%
“…Two important markers for CVD, Apo-A and Apo-B, are considered to be better predictors of CVD risk than serum HDL and LDL levels [20,26,51]. Similarly, the Apo-B/ Apo-A ratio is considered to be a better predictor of CVD risk than the total cholesterol/HDL ratio [23,26].…”
Section: Discussionmentioning
confidence: 99%
“…Since the major apolipoprotein of both LDL and VLDL is apolipoprotein B (apoB), some investigators propose using total apo B as an alternative to non-HDL-C (Barter et al 2006). These investigators cite studies suggesting that total apo B (or lipoprotein particle number) is more highly correlated with ASCVD risk than is LDL-C (Lamarche et al 1996;Moss et al 1999;Walldius et al 2001;Blake et al 2002;Rosenson et al 2002;Talmud et al 2002;Corseti et al 2004;Jiang et al 2004;Shai et al 2004;St-Pierre et al 2005) and other reports suggest that apo B is more strongly correlated with ASCVD risk than is non-HDL-C (Sniderman et al 2010(Sniderman et al , 2012. Therefore some workers contend that total apo B is the preferred target of lipid-lowering therapy.…”
Section: Ldl Cholesterol and Non-hdl Cholesterol As Major Targets Of mentioning
confidence: 99%
“…1 Mechanisms for increased CVD risk with increasing abdominal fat include the close associations of abdominal fat with metabolic CVD risk factors such as increased triglycerides (TG), as part of the insulin resistance or metabolic syndrome. 1 Some recent prospective studies have also shown that increased TG level may be an independent CVD risk factor in European [10][11][12] and US populations. 13 In recent years, Després et al 15 coined the term 'hypertriglyceridemic waist' (HTGW) to emphasize the potential predictive value of the combined increase in WC and TG in relation with CVD risk.…”
Section: Introductionmentioning
confidence: 97%